Role of Local Government in Localizing SDG in Bangladesh - Islam, Saiful (Journal of Information System and Informatics, 2024)
This study is unearthing the localizing process of SDG in Bangladesh in meeting the Sustainable Development Goals (SDGs) targets. Though nations bear the main responsibility for the SDGs, these goals specifically call for involvement from local authorities. Around 12 of the 17 SDGs require comprehensive strategies at the grassroots level to tackle interconnected issues like poverty, poor health, social challenges, and environmental degradation, with exceptions being Goals 9, 12, 13, 14, and 17. Bangladesh's constitution wisely allocates significant responsibilities for social and economic development, including the formulation and execution of plans concerning public services and economic progress, to the local government bodies, particularly the union parishad (UP), which serves as the primary interface with the community [Article 59(2)(c)(Constitution, 2004)]. Local Government Institutions in Bangladesh are positioned to have a significant influence on the localization of the SDGs, given their proximity to the most marginalized and frequently vulnerable rural communities, allowing for direct impact. Despite this potential, they have yet to make a substantial contribution to SDG localization, and with the deadline approaching, there is a pressing need to address this issue. This paper seeks to examine the obstacles encountered by local government in Bangladesh in their efforts to localize the SDGs, aiming to gain insight into the challenges hindering effective policy implementation.